Wave energy assessments in the Azores islands - Rusu, Liliana; Guedes Soares, C. (Renewable energy, 2012)
Motivated by the fact that in isolated island environments the extraction of the renewable energy becomes an issue of increasing importance, the objective of the present work is to evaluate the wave energy patterns in the Archipelago of Azores. An analysis of the wave climate in the target area is first carried out considering both remotely sensed and historical data. As a further step, a wave prediction system based on spectral wave models is implemented and validated against satellite data in the coastal environment of the archipelago. Using the above wave modelling system, the spatial distribution of the wave energy is evaluated considering relevant wave patterns for both winter and summer seasons. The results show some significant peaks of wave energy that usually occur at the western edges of the islands. Scatter diagrams are developed for some of these locations found richer in wave energy. Using these diagrams, an evaluation is made for the average energy that would be provided in the nearshore targeted locations by a PELAMIS installation. The results show that the Archipelago of Azores has considerable resources of wave energy, some of them located in the immediate vicinity of the shore. ► An evaluation of the wave energy patterns in the Azores islands is made. ► An analysis of the wave climate is carried out with remotely sensed data. ► A prediction system based on spectral wave models is implemented and validated. ► The spatial distribution of the wave energy is evaluated for both winter and summer seasons. ► An evaluation is made for the average energy that would be provided by a PELAMIS installation.